Stakeholders Training Strategy as a Key Factor of Project Costs Estimation - Katarzyna CZAINSKA; Kazimierz KOWALSKI (Communications of International Proceedings, 2020)
The authors of this article took up the subject of an incorrectly planned training strategy in projects and the consequences of this phenomenon in economic and organizational practice. As the research objective, they adopted indicating the critical role of training planning in project management. Based on literature research, case studies, and direct interviews with representatives of the military, IT, banking, logistics, and financial and development/construction industries, carried out in 2018-2020, they proposed the original method ("STOP costs"). The method of multidimensional analysis, which is a combination of well-known techniques and management tools (i.e., Stakeholders Mapping, Training Needs Analysis, Objects maintenance and Goals Management, Project Life Cycle), can be used to eliminate the problem of underestimating the training costs in project management and minimizing the negative consequences of the lack of appropriate training in all phases of the project.
Keywords: Trainings; Development; Project Management.